National Intimate Partner and Sexual Violence Survey (NISVS): General Population Survey Raw Data, 2010 ([Verlag nicht ermittelbar], 2014)
The National Intimate Partner and Sexual Violence Survey (NISVS) is an ongoing nationally representative survey that assesses experiences of sexual violence, stalking, and intimate partner violence among adult women and men in the United States and for each individual state. The survey focused exclusively on violence and collects information about Sexual violence by any perpetrator, including information related to rape, being made to penetrate someone else, sexual coercion, unwanted sexual contact, and non-contact unwanted sexual experiences Stalking, including the use of technologies such as text messages, emails, monitoring devices (e.g., cameras and GPS, or global positioning system devices), by perpetrators known and unknown to the victim Physical violence by an intimate partner Psychological aggression by an intimate partner, including information on expressive forms of aggression and coercive control Control of reproductive or sexual health by an intimate partner In addition to collecting lifetime and 12 month prevalence data on sexual violence, stalking, and intimate partner violence, the survey collects information on the age at the time of the first victimization, demographic characteristics of respondents, demographic characteristics of perpetrators (age, sex, race/ethnicity) and detailed information about the context in which these types of violence occur. The primary objectives of the survey are to describe the prevalence and characteristics of sexual violence, stalking, and intimate partner violence in the United States; who is most likely to experience these forms of violence; the context in which sexual violence, stalking, and intimate partner violence are experienced; and the consequences and impacts of these forms of violence. The data file contains 18,957 cases and 26,114 variables.